Chondrokalzinose: Idiopathisch oder Manifestation seltener metabolischer Erkrankungen? - Knitza, Johannes; Kleyer, Arnd; Schett, Georg; Manger, Bernhard (Orthopäde, 2019)
Calcification in hyaline and fibrocartilage is caused by the deposition of calcium pyrophosphate dehydrate, commonly referred to as chondrocalcinosis. Clinically, this can lead to arthritis symptoms similar to a gout attack –“pseudogout”. Nonetheless, also chronic or asymptomatic disease courses are possible. The prevalence of chondrocalcinosis increases with age. The diagnostic workup of degenerative joint disease, therefore, often reveals calcifications of articular cartilage as harmless incidental findings. However, particularly in patients younger than 60 years of age, chondrocalcinosis can be the symptom of an underlying metabolic disease. This review article highlights these rare diseases and presents unusual manifestations of chondrocalcinosis.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Calcification; physiologic; Calcium pyrophosphate deposition disease; Cartilage; articular; Epidemiology; Osteoarthritis